Non-binary worldviews in education - Bråten, Oddrun M. H. (British Journal of religious education, 2022)
In this article, I discuss the potential of developing a kind of worldview education that has the purpose of enabling teachers and students to understand how worldviews are formed. I explore how suggestions of Ann Taves can be helpful towards such an aim and pay special attention to research into self-defined ‘non-religious people. It seems their worldviews can defy the secular-religious divide and be categorised as non-binary. Taves have suggested to use worldviews as an overarching rubric, that encompasses both religious, non-religious and non-binary views, which I see as corresponding with suggestions towards worldview education in schools. It signals a need for a new language for certain parts of human activity related to meaning-making. A kind of Worldview education is already a part of school subjects in Norway, Sweden, England, Finland, Netherlands and beyond, and scholars are now exploring possibilities in this. I review some recent discussions among educationalists against the suggestions of Taves, who define worldviews in terms of Big Questions, draw upon a global meanings system theory used by psychologists, and biological and evolutionary grounding of the concepts which, according to Taves would make the worldview concept more stable than the highly contested concept of religion.